Cover crops can affect subsequent wheat yield in the Central Great Plains. Issue 3 (2nd September 2016) - Nielsen, David C.; Vigil, Merle F.; Lyon, Drew J.; Higgins, Robert K.; Hergert, Gary W.; Holman, Johnathon D.
Abstract : This research documented water use, grain yield, and water use efficiency of wheat following a 10‐species cover crop mixture and single‐species plantings (planted no‐till into proso millet residue) compared with winter wheat following a no‐till fallow period. The study was conducted under varying water availability conditions in western Nebraska and northeastern Colorado. Earn 0.5 CEUs in Soil & Water Management by reading this article and taking the quiz at www.certifiedcropadviser.org/certifications/self‐study/775 .